Comprehensive and Conservative Management of Talon Cusp: A New Technique - Ankit Arora; Padmaja Sharma; Surendra Lodha (Case Reports in Dentistry)
Talon cusp is a common dental anomaly affecting maxillary central incisors. Gradual grinding of this additional cusp is commonly followed now. Advocated below is a new technique explaining the use of air abrasion and putty index during the stepwise reduction of the cusp. The technique is advantageous in preventing patient discomfort and tracking the amount of reduction in a predictable way.